1983
DOI: 10.4141/cjps83-012
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Corn Heat Unit System for the Short-Season Growing Regions Across Canada

Abstract: A study was conducted at 11 locations across Canada to determine if corn hybrids have different corn heat unit (CHU) requirements in different climates. The study included six hybrids, four each in the three years 1977–1979. Differences in the time between planting and emergence were attributable to slow emergence of two hybrids as well as management and weather factors at different locations. Genotypic differences were expressed mainly in the period between emergence and anthesis. At three locations, 198 CHU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
3
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 8 publications
4
21
3
2
Order By: Relevance
“…The evaluated hybrids showed different duration of the emergence–flowering and flowering–physiological maturity stages. These results differ from those observed by Derieux and Bonhomme (1982a, 1982b) for the North region of Europe and by Major et al (1983) in Canada, who found that the differences in the hybrid cycle were mainly explained by changes in the duration of the period from emergence to flowering. Differences in durations of the grain‐filling period among hybrids were also found by Maddonni et al (1998)…”
Section: Discussioncontrasting
confidence: 99%
“…The evaluated hybrids showed different duration of the emergence–flowering and flowering–physiological maturity stages. These results differ from those observed by Derieux and Bonhomme (1982a, 1982b) for the North region of Europe and by Major et al (1983) in Canada, who found that the differences in the hybrid cycle were mainly explained by changes in the duration of the period from emergence to flowering. Differences in durations of the grain‐filling period among hybrids were also found by Maddonni et al (1998)…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the correlation coefficient between mean daily maximum temperatures (May through September) and the GDDAP‐R6 intervals for the hybrid 3394 was equal to 0.82 (12 environments). Several previous researchers (Aspiazu and Shaw, 1972; Major et al, 1983; Sutton and Stucker, 1974) have reported similar relationships. Thus, the hybrids appear to have the capacity to adapt to shorter‐season environments.…”
Section: Resultssupporting
confidence: 56%
“…The reproductive period (silking to physiological maturity), measured in days, is less variable than the vegetative period (Derieux and Bonhomme, 1982b); therefore, temperature response studies have focused on the vegetative period (e.g., Bonhomme et al, 1994). However, thermal-time concepts, such as the GDD and CHU, have been less useful for the reproductive period, because thermal time required for specific genotypes to reach maturity has been found to vary with the thermal environment (represented by mean daily air temperature) (Major et al, 1983;Plett, 1992).…”
mentioning
confidence: 99%